The Influence of Career Development and Transformational Leadership on Employee Sustainable Performance Moderated by the Perceived Organizational Support at the Secretariat of the Presidential Advisory Council Jakarta - Pertiwi, Dheyas Tri; Kasmir, Kasmir (Dinasti International Journal of Management Science, 2025)
This study investigates the influence of career development and transformational leadership on employee sustainable performance moderated by perceived organizational support at the Secretariat of the Presidential Advisory Council Jakarta. Employee sustainable performance represents employees' specific efforts for continuous personal and organizational growth, which is crucial for achieving long-term strategic objectives in public sector organizations. Using Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis with 113 respondents representing the entire employee population, this research employs a quantitative causal approach to examine the complex relationships between variables. The findings reveal that career development significantly contributes 34.0% to sustainable performance enhancement, with performance quality improvement through self-discipline as the dominant dimension. Transformational leadership contributes 30.5% to sustainable performance, with individual consideration as the strongest dimension reflecting leaders' care and support for employees. Perceived organizational support demonstrates a positive influence of 21.6%, where organizational recognition of employee contributions serves as the primary motivational indicator. The moderation analysis unveils intriguing dynamics where perceived organizational support plays a dual role in strengthening or weakening inter-variable relationships, creating a negative moderation on career development but positive moderation on transformational leadership, suggesting that excessive support may create dependency that hinders autonomous development initiatives while optimal support enhances inspirational leadership effectiveness.